2015
DOI: 10.1093/mutage/gev084
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofin vivoresveratrol supplementation in irradiated mice on the induction of micronuclei in peripheral blood and bone marrow reticulocytes

Abstract: The aim of the study was to investigate how coadministration of resveratrol (RSV) at different time after the start of irradiation influences the frequency of micronuclei (MN) in reticulocytes of bone marrow and peripheral blood, and if the RSV supplementation after termination of irradiation may influence the recovery process of damaged cells. Coadministration of RSV with 1-day delay after 1 Gy irradiation significantly decreased the levels of MN in bone marrow and in peripheral blood, whereas with 1-week del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…In agreement to our results, Dobrzynska et al 31 reported that irradiation and coadministration of RSV induced reduction in micronuclei in bone marrow and reticulocytes. Decrease in the DNA damage in mice reticulocytes might be attributed to proposed antioxidant mechanisms of RSV.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement to our results, Dobrzynska et al 31 reported that irradiation and coadministration of RSV induced reduction in micronuclei in bone marrow and reticulocytes. Decrease in the DNA damage in mice reticulocytes might be attributed to proposed antioxidant mechanisms of RSV.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, fractionated doses of 0.5 and 1 Gy administered to mice for 1 or 2 weeks induced MN both in the bone marrow and in peripheral blood RET. Induction of micronuclei in reticulocytes or polychromatic erythrocytes in mouse bone marrow or peripheral blood in vivo following irradiation were also observed previously at different doses and times of irradiation (Gandhi 2013; Bannister et al 2016; Dobrzyńska et al 2016). The frequency of micronuclei was similar for 0.5 Gy and lower for 1 Gy as compared to our earlier study, where the same doses of irradiation were used (Dobrzyńska et al 2016).…”
Section: Discussionsupporting
confidence: 75%
“…A concentration of 50 mg/kg BW in mice corresponds a dose of 243-324 mg in adult humans weighting 60-80 kg [98,99], respectively, and these concentrations are in the range of the concentrations commonly used for human trials and stated to be safe [96,97]. In addition, these levels are below the highest commercially available single dose of about 500 mg per tablet or capsule [100]. In vitro concentrations of resveratrol are also varying from low of 0.03 µM [20] to high doses of 100-200 µM [19], depending on the in vitro models used.…”
Section: Discussionmentioning
confidence: 92%